The effect of soil texture and root density on infiltration rate of soil - Azlina Binti Ismail (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Soil texture is simply defined as the relative proportion particles of sand, silt and clay found in the soil. These particles differ amongst each other in terms of the size. Particles that range in size from 0.05-2.0 mm are sand. Particles that fall between 0.002-0.05mm are considered silt. The smallest particles are clay, which is less than 0.002 mm in size. The relative fraction of these soil particles is important because it can determine factors such as the soil water holding capacity, drainage, and plant rooting depth. Soil texture and textural class can be determined using the textural triangle once the percentage of the soil separates is known. Two soil textures are used in this research that is sandy clay loam from fine class and sandy loam from coarse textural class. Both soil textures are obtained through sieve test by using sieve shaker. Soil texture B is the mixture of soil A and sand. This study was carried out over more than four week after corn has been planted in each soil column to investigate the effect of soil texture and root density on infiltration rate of soil. Based on the result obtained in 4 week of soil infiltration,Soil texture B showed higher of average root density in the first two weeks, but in third and fourth week , average root density was higher for soil texture A.Different soil texture has produced different rate of infiltration rate. Soil texture B (Sandy Loam) having a higher rate compared to Soil Texture A (Sandy Clay loam).This is due to the existence of crop root has modified the rate of infiltration. The crop root would filled-up the porosity of the soil, thus reducing the rate of infiltration. In fact, the infiltration rate was kept decreased as the crop grown bigger or the root density getting higher.Moreover, Soil texture B showed higher of average root density than average root density of soil texture A.